Roman rule and civic life : local and regional perspectives - Ligt, L. de; Hemelrijk, Emily Ann, 1953-; Singor, H. W. (Impact of Empire Online, ISBN: 9789004411142., 2004)
Contents: I. INSTRUMENTS OF IMPERIAL RULE. ECK, W.: Lateinisch, Griechisch, Germanisch ...? Wie sprach Rom met seinen Untertanen? TALBERT, R.: Rome's provinces as framework for world-view. KOKKINIA, C.: Ruling, inducing, arguing: how to govern (and survive) a Greek province. SLOOTJES, D.: The governor as benefactor in Late Antiquity. LIGT, L. DE: Direct taxation in western Asia Minor under the early Empire. II. CONQUEST AND ITS EFFECTS BIRLEY, A.: Britain 71-105: advance and retrenchment. ROSSUM, J.A.. VAN: The end of the Batavian auxiliaries as 'national' units. COULSTON, J.C.N.: Military identity and personal self-identity in the Roman army. BRUUN, C.: The legend of Decebalus. III. ROMANIZATION AND ITS LIMITS LOMAS, K.: Funerary epigraphy and the impact of Rome in Italy. BINTLIFF, J.L.: Town and chôra of Thespiae in the imperial age. ELTON, H.: Romanization and some Cilician cults. HESBERG, H. VON: Grabmonumente als Zeichen des sozialen Aufstiegs der neuen Eliten in den germanischen Provinzen. HAAN, N. DE: Living like the Romans? Some remarks on domestic architecture in North Africa and Britain. IV. URBAN ELITES AND CIVIC LIFE VRIES, T. DE & W.J. ZWALVE: Roman actuarial science and Ulpian's life expectancy table. KRIECKHAUS, A.: Duae Patriae? C. Plinius Caecilius Secundus zwischen germana patria und urbs. STRUBBE, J.H.M.: Cultic honours for benefactors in Asia Minor. HORSTER, M.: Substitutes for emperors and members of the imperial families as local magistrates. DONDIN-PAYRE, M.: Notables et élites dans les Trois Gaules. BRANCO, M. DI: Entre Amphion et Achille: réalité et mythologie de la défense d'Athènes du IIIe au IVe siècle. NAVARRO CABALLERO, M.: L'élite, les femmes et l'argent dans les provinces hispaniques. HIRSCHMANN, V.: Methodische Überlegungen zu Frauen in antiken Vereinen. HEMELRIJK, E.: Patronage of cities: the role of women.